EKSISTENSI KESENIAN KUDA LUMPING DI DAERAH ALANG LAWAS JORONG PARAK LUBANG KENAGARIAN TANJUNG GADANG KECAMATAN LAREH SAGO HALABAN - Tri Rahayu Zulfiana; Marzam Marzam; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2014)
Abstract This article explained about the existence of Kuda Lumping art in Alang Lawas Jorong Parak Lubang Kenagarian Tanjung Gadang Kecamatan Lareh Sago Halaban. The existence of Kuda Lumping art could be seen from the people in Alang Lawas Jorong Parak Lubang who were closely related to Kuda Lumping art especially in the great days celebrations such as in Idul Fitri. For people in Alang Lawas Jorong Parak Lubang, Kuda Lumping art had been deeply rooted and had become their need. Kuda Lumping art told people about a knight riding a horse who was a hero in Javanese Kingdom, and nowadays he was still memorized by Minangkabau people in Alang Lawas Jorong Parak Lubang. This art was still performed in Idul Fitri celebration every year. Furthermore, the existence of Kuda Lumping art could be seen from its functions in society such as for entertaining, integrating the society and for aesthetics presentation. Keyword: Eksistensi, Kuda Lumping, Perayaan Idul Fitri, Fungsi.